Urgensi dalam Meratifikasi Convention On Cybercrime sebagai Pemenuhan HAM di Indonesia - Wulan, Ida Ayu Agung Rasmi; Astariyani, Ni Luh Gede (Kertha Patrika; Vol 45 No 2 (2023), 2023)
This study aims to analyze the provisions of Indonesian legislation governing the protection of personal data relating to cybercrime or cybercrime and conduct an analysis with international instruments in the field of Cybercrime, namely the Convention on Cybercrime which has not been ratified by Indonesia and the urgency of ratifying this Convention for the harmonization of Indonesian national law. Researchers used normative legal research in this study. Researchers use laws and regulations, articles, scientific journals, and books as sources of information and library materials so that legal research is known as formative law. This study used a statutory approach and a case approach. The study findings show that Indonesia already has several types of personal data protection arrangements spread across several regulations and laws. But in fact, this does not make cases of personal data leakage in Indonesia subside. Therefore, the strategy that Indonesia must take is to first ratify or access the Convention on Cybercrime, Budapest, 2001, so that the cooperation mechanism stipulated in the convention ultimately benefits and helps Indonesia in eradicating borderless cybercrime.